2008
DOI: 10.1007/s12548-008-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maxillary molar distalization on mandibular condylar pathways

Abstract: Introduction:The objectives of this study were to determine whether maxillary molar distalization with a Pendulum appliance affects mandibular condylar pathways and whether quantitative axiographic measurements and tracings can measure these changes.Methods: Twenty Dental Class II subjects, aged 11.5-15.5, were selected for maxillary molar distalization with a pendulum appliance. Before treatment open-close, protrusion-retrusion, and left and right mediotrusion movements were recorded for each subject. Axiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…In an associated study, significant change was found in the condylar pathways following molar distalization with a Pendulum appliance [11]. However, no significant change was recorded in this study for various measurements of cervical posture.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In an associated study, significant change was found in the condylar pathways following molar distalization with a Pendulum appliance [11]. However, no significant change was recorded in this study for various measurements of cervical posture.…”
Section: Discussioncontrasting
confidence: 67%
“…Changes secondary to upper molar distalization with a Pendulum appliance have been reported, these include a cephalometric analysis of the head [4], a cast and cephalometric analysis [16], a cast and cephalometric analysis of unilateral distalization [33] and an axiographic analysis of condylar movement [11]. It has not been reported whether cervical posture is altered as a consequence of maxillary molar distalization with a Pendulum appliance.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the results of this study, the upper molars distalization technique performed with clear aligners seems to overcome various side effects related to this orthodontic procedure typically observed with other appliances [ 11 , 49 ] and seems to allow a predictable distal body movement of upper molars with control of the TMJ parameters. This could be related to the aligner design, which enables the control of 3D movements by holding teeth on all the surfaces (occlusal, vestibular, and palatal/lingual) and applying proper forces thanks to properly digitally planned attachments.…”
Section: Discussionmentioning
confidence: 80%
“…The thickness of aligners and the impact of the biting block of aligner material may explain the nonexistence of a significant vertical dimension increase [ 53 ]. The insignificance of our finding could be interpreted as molar distalization by clear aligners associated with the absence of molar extrusion and clockwise rotation of the occlusal plane in contrast with conventional appliances [ 11 ]. This would lead to premature contact and sudden alteration of temporomandibular components’ relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation